THE IMPORTANCE OF FINANCIAL AND CREDIT MECHANISMS IN THE MANAGEMENT OF THE STATE - Toshanov Shuxrat Jontemir ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Financial and credit mechanisms play a crucial role in the effective management of a state. These mechanisms act as the backbone of a nation's economic stability and growth, enabling the government to fulfill its responsibilities towards its citizens and achieve its development goals. This article will delve into the significance of financial and credit mechanisms in state management, exploring their diverse functions and highlighting their impact on various aspects of governance.